Designing An Android Attendance Application For Employees Of The Sub-District KUA Putri Hijau North Bengkulu - Mohammad Abkar Nur Rohman; Dandi Sunardi; Ardi Wijaya; Surya Ade Saputera (Jurnal Komputer, Informasi dan Teknologi, 2024)
This thesis aims to design an Android application specifically developed for attendance activities at the Kantor Urusan Agama (KUA) Putri Hijau District North Bengkulu, using the MIT App Inventor platform. This application is expected to be more efficient than the old application and can provide convenience for employees who want to run attendance and make it easier for the admin to recap attendance data. To achieve this research, researchers use the Prototype method with code block programming development in MIT App Inventor and use Googel maps assistance in validating attendance locations. In the implementation process, the author will focus on designing an interface that is simple and easy to understand, ensuring compatibility with Android devices, and integrating features that are relevant to the needs of Attendance and Licensing. The importance of creating an application that can be accessed without difficulty by users without a conventional programming background is a major concern. Therefore, this research will prioritize the use of visual programming provided by MIT Inventor, enabling application development without the need for in-depth knowledge in programming. The result of this research is an Android Attendance application design that can be used by Admin and Employees at the Office of Religious Affairs Putri Hijau District, North Bengkulu. This application is expected to provide benefits for KUA Admins and Employees in terms of reducing the number of employees.